(untitled) (Vietnam Journal of Community Medicine, 2024)
Exposure to chromium in the workplace can lead to severe health consequences, including skin diseases, respiratory problems. Objective: to assess the current status of chromium exposure and some health effects in cement industry workers. Subject and method: This cross-sectional study, conducted from 2022 to 2023, involved 255 workers exposed to chromium (Cr) in the workplace at three cement plants. Results: The proportion of workers exposed to chromium (VI) > 50 µg/m3 accounted for 20% and urinary chromium ≥ 25 µg/L accounted for 17.3%.The prevalence of skin diseases and restrictive ventilatory disorders among cement workers was 12.2% and 23.1%, respectively. The prevalence of ear, nose, and throat symptoms among workers exposed to chromium dust was relatively high at 35.7%. The median urinary chromium concentration in the dermatological group was 14.12 µg/L. The group of workers with dermatological diseases had a urinary chromium concentration difference of ≥ 25 µg/L that was 3.18 times higher than that of the group without dermatological diseases, with 95% CI of 1.40-7.25%. Not yet relationship was found between urinary chromium and ventilation disorders-ear-nose and restrictive ventilatory disorder diseases. Conclusion: There is a strong association between urinary chromium levels and the risk of developing dermatological diseases.